2013
DOI: 10.2147/ppa.s51299
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of insulin initiation for type 2 diabetes in France: analysis of the National Health and Wellness Survey

Abstract: BackgroundThe aim of the study was to identify the intrinsic patient characteristics and extrinsic environmental factors predicting prescription and use and, more specifically, early initiation (up to 5 years of disease duration) of insulin for type 2 diabetes in France. A secondary objective was to evaluate the impact of insulin therapy on mental and physical quality of life and patient adherence.MethodsThe data used in this study were derived from the 2008, 2010, and 2011 France National Health and Wellness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 39 publications
5
33
1
2
Order By: Relevance
“…After controlling for treatment type, patient characteristics and laboratory assessments, the only significant comorbid condition associated with earlier insulin use was obesity. This is actually contrary to other literature that did find a positive association between insulin use and a range of other comorbidities 4, 7, 9, 11, 13; however, none of these previous studies used propensity score matching. Notably, Fu et al.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…After controlling for treatment type, patient characteristics and laboratory assessments, the only significant comorbid condition associated with earlier insulin use was obesity. This is actually contrary to other literature that did find a positive association between insulin use and a range of other comorbidities 4, 7, 9, 11, 13; however, none of these previous studies used propensity score matching. Notably, Fu et al.…”
Section: Discussioncontrasting
confidence: 96%
“…The finding that HbA1c was significantly associated with insulin initiation is not surprising and is consistent with a number of previous studies 2, 8, 9, 10, 11, 12, 13, 14, 15. After controlling for treatment type, patient characteristics and laboratory assessments, the only significant comorbid condition associated with earlier insulin use was obesity.…”
Section: Discussionsupporting
confidence: 89%
“…In developed countries the peak incidence for type 2 diabetes is noted in adults aged about 65 years (Wild, Roglic, Green, Sicree, & King, 2004). Thus, patients significantly younger may perceive the disease as more burdensome and stigmatizing (Skinner et al, 2011), and insulin therapy as interfering with their occupational career (Reach et al, 2013) or social life, which would contribute to increasing NA. As compared to the "no response" subgroup, patients from the ambivalent subgroup representing "challenge response" rated their material status lower and more often had vocational education.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported either no change in the patients' quality of life (de Grauw, van de Lisdonk, van Gerwen, van den Hoogen, & van Weel, 2001;UKPDS 37, 1999) or negative mood changes including problems with social functioning, greater emotional fatigue and perceived burdensomeness of the treatment (Goddjin et al, 1999;Reach, Le Pautremat, & Gupta, 2013;de Sonnaville et al, 1998), as well as increased tension, but only in patients with more frequent hypoglycemic episodes (UKPDS 37, 1999). Opposite effects were also noted, i.e.…”
mentioning
confidence: 99%
“…Clinicians recommend insulin therapy to achieve successful glycemic control for diabetes mellitus (DM), as it can compensate for adequate plasma glucose levels and reduce the micro/macrovascular complications of DM [1]. Unfortunately, many patients may delay beginning insulin therapy because of misconceptions about insulin and attitudinal barriers such as fears of needles or social stigma [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%